Incidence of Congenital Heart Disease in Pediatric Age Group Following Maternal Use of Luteal Supportive Hormonal Therapy During Pregnancy - Huntush, Zina Saleam (Indonesian Journal on Health Science and Medicine, 2025)
The most prevalent birth abnormality, congenital heart disease (CHD), affects 9.4 out of 1000 babies, Certain medications, such as phenytoin, lithium, amphetamines, warfarin, oestrogen, or progesterone, have been shown to raise the risk of congenital heart disease in offspring when used by the mother during pregnancy. Identify the incidence of Congenital Heart Disease in pediatric Following Maternal Use of luteal supportive Hormonal Therapy During Pregnancy. Retrospective research was conducted at a private cardiologist's clinic between February 12 and May 1, 2025. A pre-tested questionnaire was used to interview the mother or caregiver of each kid. It asked about the mother's medical history about associated conditions, the child's sociodemographics, and whether the mother had taken luteal supporting hormone during pregnancy. The kind of CHD and the history of progesterone usage (time, duration, and route) were ascertained by echo. This study regarding socio-demographic characteristics and showed that females were more than males (55%, 45%, respectively), found that 71.76% of the patients were under one year old, VSD was the most prevalent kind of CHDs in this study (28% of the cases), also, study reflect positive correlation between progesterone and CHD. Conclude of study result most of child with CHD was less than 1 years in age and there is associate between maternal progesterone intake and fetus born with CHD. Highlights: Ventricular septal defect (VSD) was the most common congenital heart disease observed, accounting for 28% of cases. A positive correlation was found between maternal progesterone intake during pregnancy and the occurrence of CHD in offspring. Most affected children were under one year old, with a slight female predominance (55%).